Pretreatments and syruping methods for dehydrated candied santol (Sandoricum Koetjape) - How, Mary Jane F. (1983)
The effect of two anti-browning and three sugar/syrup treatments on dehydrated candied santol were determined. The two anti-browning treatments were blanching and sulfiting. The three sugar/syrup treatments are: 1) the dry method using sugar in a 1:1 fruit: sucrose ratio; 2) the quick method using 70°Bx syrup; and 3) the slow or step-up process using 50 Bx, then 60 Bx then 70 Bx syrup. Drying in a cabinet dryer (49°-65°C or 120°C-150°F) followed until constant weight was attained. A total of nine products, including control, were produced; thus an incomplete block design was used in the evaluation of the samples. Panelists evaluated the products in terms of color, texture, sweetness/sourness, santol taste and general acceptability; they also ranked them according to preference. Phase I was the choice of the best combination of anti-browning and sugar/syrup treatments. The panelists preferred the step-up or slow method in all attributes except color, not much difference due to anti-browning treatment was observed. Phase II was a closer analysis of the preferred method. Aside from the soluble solids, moisture content, titrable acidity, color and texture measurements performed in Phase I, enzyme activity, residual sulfite and equilibration time were also determined. Results showed that the syrup equilibrium could be attained after at least 5 to 7 hours. The moisture content of the dried product ranged from 8.4-12.3% after 5 to 7 hours drying in a cabinet dryer at 48.8-65.5°C (120-150°F). The tritable acidity ranged from 0.0724-0.0984% as citric acid; soluble solids from 68.2-76.3. The blanching process was adequate; residual sulfite was 14-28%. Sensory evaluation followed a randomized complete block design for the six samples -- three trials each of the step-up process using sulfiting and blanching as the anti-browning treatments. The judges found that the products differed in color and texture using the descriptive scorecard method, however, using the triangle test sight out of the twenty chose the odd samples correctly.